Experience of women in labor with premature rupture of membranes: scoping review - Okta Zenita Siti Fatimah; Andari Wuri Astuti (Universitas Aisyah Pringsewu, 2023)
The study of Premature Rupture of Membranes (PROM) in the classic mid-trimester preterm pregnancy is characterized as the breaking of the fetal layers before 28 weeks of incubation (BB) with oligo/anhydramnios. This complicates around 0.4-0.7% of all pregnancies and is related with very high neonatal mortality and morbidity rates. Concurring to the World Health Organization (WHO), the frequency of PROM globally was evaluated to be 50-60% in 2014 (WHO, 2015). In Indonesia, the rate of PROM ranges from 4.4-7.6% of all pregnancies. The rate of PROM in preterm pregnancy ranges from 3-18%, while in term pregnancies, it is estimated to be around 8-10%. In 2018, the rate of PROM in Indonesia was estimated to be 4.5% -6% of all pregnancies. Another study conducted in Indonesia found that 5-10% of all pregnancies experience PROM, and a third of deliveries that occur within less than a month are affected by PROM. 60% of PROM cases occur during full-term pregnancy, with most cases being discovered during this stage. The objective of this literature review is to survey the prove related to the experiences of mothers giving birth with PROM. This research was conducted by selecting journals concurring to consideration and prohibition criteria and using the Prisma Literature Review Flow Diagram. The experiences of mothers giving birth with PROM are described in two aspects: the characteristics of mothers giving birth with PROM (such as age, parity, work activity, gestational age) and factors related to PROM (sexual patterns, maternal and fetal genetic variations, infections, exposure to PM.25 ambient, and history of PROM). Abstrak: Ketuban Pecah dini (KPD) klasik mid-trimester preterm dideskripsikan sebagai hancurnya selaput ketuban janin sebelum usia masa hamil 28 minggu (BB) dengan oligo/anhidramnion; itu mempersulit sekitar 0,4-0,7% dari semua masa hamil dan berhubungan dengan kematian dan morbiditas neonatal yang sangat tinggi. Menurut Organisasi Kesehatan Dunia (WHO) angka terjadinya Ketuban Pecah dini (KPD) di dunia tahun 2014 sebanyak 50-60% (WHO, 2015). KPD di Indonesia berkisar 4,4 –7,6% dari keseluruhan masa hamil. Angka terjadinya KPD berada diantara 3-18% yang terjadi pada masa hamil preterm, sedangkan pada masa hamil aterm sekitar 8-10%. Insiden KPD di Indonesia berada diantara 4,5%-6% dari seluruh masa hamil tahun 2018. Hasil pengkajian lain di Indonesia bahwa dari seluruh masa hamil, 5–10% mengalami KPD. Pada persalinan kurang bulan, sepertiga diantaranya mengalami KPD. 60% KPD di antaranya terjadi pada masa hamil cukup bulan. Pada masa hamil dengan KPD, sebagian besar kasus ditemukan. Tujuan : Literatur review ini bertujuan untuk Untuk mereview evidence terkait dengan Pengalaman Ibu melahirkan dengan Ketuban Pecah dini. Method pengkajian : Method penelitan ini dilakukan dengan cara menyeleksi jurnal sesuai dengan kriteria inklusi dan eksklusi dan dilakukan dengan menggunakan Diagram Flow Literature Review PRISMA. Pengalaman ibu melahirkan dengan KPD digambarkan dalam dua aspek yakni sifat ibu melahirkan dengan Ketuban Pecah dini (usia, paritas, aktifitas kerja, umur masa hamil) dan faktor yang berhubungan dengan kpd (pola seksual, variasi genetik ibu dan janin, infeksi, paparan PM.25 ambien, dan riwayat KPD).